La déglaciation et le relèvement isostatique sur la côte est de la baie d’Hudson - Claude Hillaire-Marcel (Cahiers de géographie du Québec, 2005)
On the eastern coast of Hudson Bay, in the area between Great-Whale-River and the Richmond Gulf, the last wisconsinian ices flowed westward. The deglaciation took place between 8.100 l*C yr BP (Great-Whale-River) and 7.600 1 4 C yr BP (Richmond Gulf). The maximum limit of the Tyrrell Sea rises toward the south-east, from 230 m (north of Richmond Gulf) to 315 m (north of Manitounuk sound). In the Richmond Gulf, 185 successive raised beaches were built during the emergence of the land which followed the deglaciation. A 45 yr periodicity appears in their construction. Correlation between ï 4 C and sideral ages are in agreement with Suess' curve (1970). The emergence curve, established from the raised beaches, indicate a multiple component isostatic uplift. The land, first tilted toward NNE, is uplifted in relation to the main wisconsinian ice load on south-eastern Hudson Bay at the beginning, and later in relation to the more recent ice center of New Québec. The isostatic rate of uplift decreases from the 6,5 cm/yr at 6.000 14C yr BP, to a present rate of 1,1 cm/yr. A 20 m eustatic rise is observed between the deglaciation and 6.000 14C yr BP, when the sea level seemed similar to the present one. Variations in the rate of sea level changes indicate secondary eustatic oscillations of metric amplitude, which correspond to the main climatic events of that period of the Holocene. Sur la côte orientale de la baie d'Hudson, dans la région située entre Poste-de-la-Baleine et le golfe de Richmond, les dernières glaces wisconsiniennes se sont écoulées vers l'ouest; la déglaciation s'effectuant entre 8.100 ans 14C BP (Poste-de-la-Baleine) et 7,600 ans 14C BP (golfe de Richmond). L'altitude maximale atteinte par la mer postglaciaire de Tyrrell s'élève vers le sud-sud-ouest, passant de 230 m au nord du golfe de Richmond à 315 m à l'extrémité nord du détroit des Manitounuk. Au golfe de Richmond, 185 plages soulevées marquent l'émersion des terres depuis la déglaciation. On a pu mettre en évidence une périodicité de 45 ans ...